Report of Insular Comission - Todd, Roberto H.; Waskins, Char W.; Curtis, H. G. (My University, 1899)
Report of Insular Commission from Roberto P. Kennedy, Char W. Waskins and H. G. Curtis
Keywords: Municipal government--Puerto Rico.; Gobierno Municipal--Puerto Rico.; Education--Puerto Rico.; Educación--Puerto Rico.; Puerto Rico--Economic conditions.; Religion--Puerto Rico.; Military services--Puerto Rico.; Puerto Rico. Department of Justice.